Interpretation of the Meaning of the Ḥadīth on ‘Aqīqah in the Perspective of Muhammad Shahrur’s Hermeneutics of Naẓariyyat al-Ḥudūd - Arjunaedi, Arjunedi; Wilwadikta, Qur’ani Parang (Canonia Religia, 2025)
This study examines the interpretation of the meaning of the ‘aqīqah hadith using the hermeneutic approach of Muhammad Syahrur's hudud theory. The study analyzes the understanding of hadiths about ‘aqīqah narrated in the primary hadith collections, using the theoretical framework of boundaries (naẓariyyat al-hudūd) developed by Muhammad Syahrur. Through a qualitative research method with a library approach, this study reveals that interpreting the aqiqah hadith from the perspective of Syahrur's hudud theory results in a more contextual and flexible understanding. This theory views the stipulation of aqiqah animals (two for boys and one for girls) as the maximum limit (ḥadd al-a'lā), not a rigid requirement. The timing of the aqiqah is also understood more flexibly within the minimum boundary (ḥadd al-adnā), the seventh day after birth, extending to the maximum limit adjusted to one's ability and welfare. This research contributes to a new perspective on understanding the ‘aqīqah hadith, which is more adaptive to contemporary contexts while still adhering to the principles of Sharia.